2019
DOI: 10.1093/mnras/stz154
|View full text |Cite
|
Sign up to set email alerts
|

ATLASGAL – molecular fingerprints of a sample of massive star-forming clumps★

Abstract: We have conducted a 3-mm molecular-line survey towards 570 high-mass star-forming clumps, using the Mopra telescope. The sample is selected from the 10,000 clumps identified by the ATLASGAL survey and includes all of the most important embedded evolutionary stages associated with massive star formation, classified into five distinct categories (quiescent, protostellar, young stellar objects, HII regions and photo-dominated regions). The observations were performed in broadband mode with frequency coverage of 8… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 99 publications
4
24
0
Order By: Relevance
“…The well separated cumulative distributions of C 2 H/c-C 3 H 2 show that the relative intensities of the small hydrocarbons increase with the evolution of high-mass clumps. This trend is also found for ATLASGAL sources in the southern hemisphere (Urquhart et al 2019).…”
Section: Line Widths and Integrated Fluxessupporting
confidence: 69%
See 1 more Smart Citation
“…The well separated cumulative distributions of C 2 H/c-C 3 H 2 show that the relative intensities of the small hydrocarbons increase with the evolution of high-mass clumps. This trend is also found for ATLASGAL sources in the southern hemisphere (Urquhart et al 2019).…”
Section: Line Widths and Integrated Fluxessupporting
confidence: 69%
“…Integrated intensity ratios of molecular lines have been used as a chemical clock tracing different evolutionary sequences of high-mass stars in molecular clumps (e.g., Rathborne et al 2016;Urquhart et al 2019). With the assumption that observed lines are optically thin, integrated intensity ratios gives us approximate abundance ratios of molecular lines compared with each other.…”
Section: Line Widths and Integrated Fluxesmentioning
confidence: 99%
“…In the 1D physical-chemical modeling of HMSFRs with MUSCLE by Gerner et al (2014), CH 3 CN and CH 3 OH are cospatial in radial abundance profiles toward the inner hot core region. Urquhart et al (2019) find that the line integrated ratios of S-and N-bearing species are positively correlated with the dust temperature in a sample of high-mass star-forming clumps. Gratier et al (2013) found that CH 3 CN is much more abundant in the photo-dissociation region (PDR) of the Horsehead nebula than the associated cold and dense core.…”
Section: Correlations Between Chemical Speciesmentioning
confidence: 75%
“…Approximately 10 000 dense clumps have been identified from the ATLASGAL maps Urquhart et al 2014a). Many of these have since been followed-up with molecular line observations to obtain radial velocities (Wienen et al 2012;Csengeri et al 2016;Wienen et al 2018;Urquhart et al 2018Urquhart et al , 2019, which when combined with a Galactic rotation curve can be used to calculate kinematic distances and derive physical properties (Wienen et al 2015). Images from the HiGAL survey (Molinari et al 2010;Molinari et al 2016) have been used to fit the spectral energy distributions (SED), to determine the dust temperatures and bolometric luminosities of the embedded protostellar objects (König et al 2017).…”
Section: Atlasgal Surveymentioning
confidence: 99%